ln(x-1)-ln(x+1)=2

Simple and best practice solution for ln(x-1)-ln(x+1)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x-1)-ln(x+1)=2 equation:


Simplifying
ln(x + -1) + -1ln(x + 1) = 2

Reorder the terms:
ln(-1 + x) + -1ln(x + 1) = 2
(-1 * ln + x * ln) + -1ln(x + 1) = 2
(-1ln + lnx) + -1ln(x + 1) = 2

Reorder the terms:
-1ln + lnx + -1ln(1 + x) = 2
-1ln + lnx + (1 * -1ln + x * -1ln) = 2
-1ln + lnx + (-1ln + -1lnx) = 2

Reorder the terms:
-1ln + -1ln + lnx + -1lnx = 2

Combine like terms: -1ln + -1ln = -2ln
-2ln + lnx + -1lnx = 2

Combine like terms: lnx + -1lnx = 0
-2ln + 0 = 2
-2ln = 2

Solving
-2ln = 2

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Divide each side by '-2n'.
l = -1n-1

Simplifying
l = -1n-1

See similar equations:

| 10x+15y=6 | | 0x+15y=6 | | 8d-(2+d)=42 | | 3p+2q=17 | | 8-7+3= | | 34.4*42= | | d-1-15=45 | | -8z-64=72 | | 2(7x+1)=58 | | b-718=115/6 | | 15Y+4=3Y-8 | | b-7-1/8=11-5/6 | | Y=sin^3(4x)cos(4x) | | 1.4*b=b+8 | | 3ab+6= | | -15+2n=73 | | 3(x+5)-6=x-7 | | -3n^2(-2n^5+5n-5)= | | 7x=-13 | | 12x+1y=94 | | -200+25(4)= | | 6(2z+3)=-54 | | -200+25(2)= | | -(9x-8)=-5(3x-10) | | 3b-(b+2)=5-(3-b) | | (4y+3)=(y-2) | | 21x-5=7+15y | | 7(6x+10)=280 | | 9a^2(-5a^3+5a-5)= | | 4-8a=4(1-2a) | | 4sin^2(x)=2 | | 3g+5=7b-7.4 |

Equations solver categories